PENGARUH TELEWORKING, MOTIVASI BEKERJA, DAN KETERIKATAN KARYAWAN TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA PT CIPUTRA BALAI PROPERTY) - Ivan Prayoga Eka Putra (2023)
Employee performance is the result of a person's work in quality and quality in accordance with predetermined standards based on the responsibilities given. The phenomenon taken is a decrease in employee performance at PT Ciputra Balai Property. This research is a quantitative study with the aim of analyzing and proving the effect of Teleworking, Work Motivation, and Employee Engagement on Employee Performance in the case study of PT Ciputra Balai Property. This study used a population of PT Ciputra Balai Property employees in the Business Development, Marketing, HRD, and Finance & Accounting sections of 170 respondents. The sample in this study used 120 respondents who were selected through a probability sampling technique or a sampling technique that provides equal opportunities for each element or member of the population to be selected as a sample. The data in this study were obtained from distributing questionnaires which would be analyzed using the Partial Least Square (PLS) method and assisted by using the SmartPLS application.